Old Mosque in a Religious City: Masjid Jami’ Tua Palopo as a Center of Da’wah Development - Muhammad Ilyas (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
The crisis in the role of the mosque needs to be scrutinized so that it needs to be seen again as an agent of transformation for the ummah by expanding its roles and functions again. This research aims to raise the facts and phenomena at the Jami’ Tua Palopo mosque as well as its role and efforts as a center for the development of da’wah for the people of Palopo City. The method used was descriptive qualitative using data from interviews with mosque administrators, then the data is analyzed using triangulation techniques. The results of this study concluded that the Masjid Jami’ Tua Palopo had carried out its role and function as a center for da’wah development. Some of the programs implemented include; 1) aspects of understanding of community, namely by carrying out the process of converting non-Muslim communities and fostering converts, 2) aspects of education improvement, namely by establishing Taman Pendidikan Al-Quran (TPA, Quranic Learning for Preschool), 3) social aspects shown by distributing qurban and zakat and other social activities such as the distribution of groceries during the COVID-19 pandemic.